El calendario adivinatorio de 260 días en la sociedad maya contemporánea: usos, funciones y estructura (Altre Modernità, 2013)
The goal of this article is to study the concept of time in the Maya culture, particularly in the today communities of k’iche’ area in Guatemala. Based on a fieldwork in Mexico and in Guatemala, it will be analyzed the prophetic use of the present calendar of 260 days and the concept of past, present and future prophecy and divination, through the consultation of the holy calendar cycle of tsolk’iin.The purpose is also to study the connections between the Maya Calendar and the Maya movements for the ethnic claims, as well as their political implications. Furthermore, it will be analyzed the strategic date of December, 21st 2012, which, further the present k’iche’ calendar, is falling on a day 4 Ajpuu, which a special day, used to ask for fertility and to plan future projects. It is also a day dedicated to the ancestors’ worship, a ritual always connected to the renovation and to the request of life protection, but never to the destruction and to the death.